Peace education in a conflict-affected society : an ethnographic journey - Zembylas, Michalinos; Charalambous, Constadina; Charalambous, Panayiota (Cambridge, United Kingdom ; New York : Cambridge University Press, 2016)
"Peace education initiatives have been subject to heated public debate and so far the complexities involved have not been fully understood. This multilayered analysis examines how teachers negotiate ideological, pedagogical and emotional challenges in their attempts to enact a peace education policy. Focusing primarily on the case study of conflict-affected Cyprus, Michalinos Zembylas, Constadina Charalambous and Panayiota Charalambous situate the Cypriot case within wider theoretical and methodological debates in the field and explore the implications of their findings for theory and practice. Building on current anthropological approaches, the authors use insights from policy studies and sociolinguistics to examine peace education agendas and the ways these are shaped by the dynamics of local politics and classroom practices. This study will be valuable reading for researchers of peace and policy studies as well as for practitioners and policy makers involved in introducing peace education initiatives that challenge teachers' long-held beliefs"--
Machine generated contents note: Introduction; Part I. Setting the Scene: Theory, Methodology and Context: 1. Conceptualizing 'peace education' in conflict-affected societies; 2. Designing a peace education research project; 3. The emergence of the new peace initiative in the context of Greek-Cypriot education policy; Part II. Teachers' Responses to a Peace Education Initiative: 4. Teachers' interpretations of the transition to the new policy initiative; 5. Teachers' stances and repertoires towards reconciliation; 6. Teachers' difficulties and emotions towards the new policy initiative; Part III. Mapping Teachers' Practices in a Changing Context: 7. The schooling of emotion and memory in classroom interaction; 8. Talking about peace and conflict in a (super)diverse classroom; Part IV. The Impact of Teacher Training Workshops: 9. Handling teachers' discomfort during peace education workshops; 10. Doing 'leftist propaganda' or working towards peace? Responding to teachers' resistance; 11. Moving towards critical ambivalence: enduring reservations and signs of change; Epilogue.
Includes bibliographical references and index.
Keywords: Peace -- Study and teaching -- Cyprus; Peace-building -- Cyprus; Education and state -- Cyprus